1990
DOI: 10.1093/ndt/5.9.812
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporin-Induced Renal Magnesium Leak in Renal Transplant Patients

Abstract: Renal transplant patients (n = 116) attending an outpatients clinic were screened for hypomagnesaemia. No azathioprine-treated patients (n = 46) but 24% (17 of 70) of the cyclosporin treated patients were hypomagnesaemic. The hypomagnesaemia in all cases was associated with a renal magnesium leak. This leak did not correlate with plasma bicarbonate, urate, calcium, cyclosporin or creatinine concentrations, nor did it correlate with the use of loop diuretics or duration of the transplant. A renal magnesium leak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Most of our patients with chronic renal disease had mild to moderate renal failure, and normomagnesemia as expected [1]. The lower than normal values of serum tMg and Mg 2+ in renal transplant patients can be explained by cyclosporine-induced urinary magnesium wasting [3, 4]. Due to this magnesium leak, even magnesium substitution has been recommended for patients on cyclosporine [4, 13].…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Most of our patients with chronic renal disease had mild to moderate renal failure, and normomagnesemia as expected [1]. The lower than normal values of serum tMg and Mg 2+ in renal transplant patients can be explained by cyclosporine-induced urinary magnesium wasting [3, 4]. Due to this magnesium leak, even magnesium substitution has been recommended for patients on cyclosporine [4, 13].…”
Section: Discussionmentioning
confidence: 83%
“…Hypermagnesemia is common in advanced renal insufficiency, whereas serum magnesium levels are usually normal in mild to moderate renal function impairment due to compensatory decrease in tubular reabsorption [1, 2]. Subnormal magnesium levels have been reported in renal transplant recipients receiving cyclosporine [3, 4, 5]. …”
Section: Introductionmentioning
confidence: 99%
“…The broad range can be the result of the fact that dietary Mg intake was not standardized, in view of the difficulty in enforcing strict nutritional restrictions in outpatients, and the fact that there are thus resultant broad day-to-day variations in Mg excretion. Peak serum Mg concentrations were lower in [20] related to a defective renal tubular system because of ischemia and the nephrotoxicity of various drugs especially ciclosporine [7,10,16]. The loading-test was applied to answer the question of whether there is magnesium deficiency or not.…”
Section: Discussionmentioning
confidence: 99%
“…Their mean Mg retention was 6.3 ± – 10.3% and the 0.025 and 0.975 fractiles were –19.5% and 27.5% of the loading dose, significantly less than the same investigative group found in the patients population [18]. Because even 8 hours infusion of the Mg load is unsuitably long for outpatients, we have undertaken studies of 1‐hour Mg infusion in healthy volunteers [19] and in patients who had undergone renal transplantation with (Mg wasting) immunosuppressive drug therapy [20]. Presented here are additional details on those studies, with the addition of comparative retention and bone Mg level data on hip replacement patients.…”
Section: Introductionmentioning
confidence: 99%
“…Most investigators assume that hypomagnesemia is a conse quence of a higher urinary fractional excretion rate [6][7][8]12], but some others believe that it is due to a shift of magnesium (Mg) into Mg-rich organs such as skeletal muscles, liver or kidney [5,9,10]. Only a few authors reported no significant alterations in serum Mg levels fol lowing long-term Ci treatment [13][14][15], but a decrease during the first week of treatment [13,14].…”
Section: Introductionmentioning
confidence: 99%